(untitled) (In situ, 2024)
The paper presents the preliminary results of the archaeological research conducted during the reconstruction of Dr. Franje Tuđmana Street in Zadar. Despite the fact that the aforementioned road passes through the heart of the Roman-era necropolis of Zadar, a relatively small number of graves from the Roman period were found. The main reason for this is that most of the excavation, mostly 120 to 150 cm deep, encompassed the layers of the recent filling. Small scale archaeological excavations were carried out in the area next to the monastery of St. Ivan. Within the 46 m2 trench nine inhumation graves were defined and investigated. The results of the 14 C analysis date one of the burials in period between 1634 and 1794.